Audit of Clinical Care for Women with Preeclampsia or Eclampsia and Perinatal Outcome in Ethiopia: Second National EmONC Survey - Meazaw MW; Chojenta C; Taddele T; Loxton D (Dove Medical Press, 2022)
Maereg Wagnew Meazaw,1,2 Catherine Chojenta,2 Tefera Taddele,3 Deborah Loxton2 1Maternal and Child Health Directorate, Federal Ministry of Health, Addis Ababa, Ethiopia; 2Centre for Women's Health Research, School of Medicine and Public Health, College of Health, Medicine and Wellbeing, University of Newcastle, Newcastle, Australia; 3Health System and Reproductive Health Directorate, The Ethiopian Public Health Institute, Addis Ababa, EthiopiaCorrespondence: Maereg Wagnew Meazaw, The University of Newcastle, University Drive, Callaghan, NSW, 2308, Australia, Tel +61 402 290 013, Email mulemar12@gmail.comBackground: Preeclampsia and eclampsia contribute to maternal and perinatal morbidity and mortality, especially in developing countries. However, the evidence on clinical practice in the management of preeclampsia/eclampsia and perinatal outcomes is limited. Therefore, the aim of this study was to assess clinical care and perinatal outcomes for women with preeclampsia/eclampsia admitted to health facilities in Ethiopia.Methods: This study used the 2016 Emergency Obstetric and Newborn Care survey, which included 3804 health facilities. The last two cases of women with preeclampsia/eclampsia who were admitted for birth in each participating health facility were selected and their medical records were reviewed. Descriptive analyses by health facility type, location and management authority were conducted. A chi-squared test was used to test for differences.Results: Out of the 3804 health-care facilities across the country, we could review a total of 959 medical records of women with preeclampsia or eclampsia. Of all cases, 90% (863) were hospitalised in public health facilities, 542 (56.6%) were admitted at health centre/clinics and 638 (66.3%) were in urban health facilities. A substantial proportion of maternal and newborn information was missing from their medical records. Of the 553 records that recorded perinatal outcomes, the proportion of perinatal mortality prior to discharge was 16.3% (95% CI: 13.4%, 19.6%). A significant perinatal death was recorded among mothers admitted to hospitals (P < 0.01), maternal age 15- 24 (P < 0.04), facilities in urban areas (P < 0.01), referred cases (P < 0.007), high systolic and diastolic blood pressure (P < 0.001), unconscious and experience seizure (P < 0.001), newborn with morbidity (P < 0.001), and women who spent more hours before giving birth (P < 0.002).Conclusions and Recommendations: High perinatal mortality in health facilities was reported and care toward mothers with preeclampsia/eclampsia was limited. Strengthening the health facility readiness to respond for management with data registration and reporting system needs to be improved for evidence-based decision-making on perinatal and maternal health.Keywords: preeclampsia, eclampsia, perinatal mortality, Ethiopia, EmONC